OPOSISI BINER DALAM INTERAKSIONISME SIMBOLIK PADA CERITA PENDEK “TENTANG PEREMPUAN (TPT)” KARYA BENNY ARNAS - Dian Susilastri (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2019)
This article discusses about the short story of TPT by Benny Arnas. It uses the concept of symbolic definition of George Herbert Mead’s perspective of symbolic interactions involving mind, self, and society. The definition of the symbol, in this case, must be the same among participants. If there is any difference, it would potentially raise conflicts and the dissimilarity of the symbol definition would be described. The method used in this data analysis is descriptive-analysis. The result shows that there is binary opposition towards symbol meaning in the interaction among participants. It reveals that there is a conceptual conflict about the characters’ point of view on the same symbols.